Conductivity and structural studies of plasticized polyacrylonitrile (PAN) – lithium triflate polymer electrolyte Films - Ahmad .A; Md. Isa .K.B; Osman .Z (Universiti Kebangsaan Malaysia, 2011)
The effect of different plasticizers on the properties of PAN–LiCF3SO3 polymer electrolytes has been studied. Propylene carbonate (PC) and ethylene carbonate (EC) having different values of donor numbers, dielectric constant and viscosity have been used as plasticizers. The highest room temperature conductivity for the film in the PAN–LiCF3SO3 system was 3.04 × 10-4 S cm-1. The highest room temperature conductivity for the films in the PAN–EC–LiCF3SO3 system and the PAN–PC–LiCF3SO3 system was 1.32 × 10-3 and 8.64 × 10-4 S cm-1. The addition of plasticizers has been found to enhance the conductivity of polymer electrolytes by increasing the amorphous content as well as by dissociating the ion aggregates present in polymer electrolyte. Conductivity temperature-dependence studies of these plasticized PAN-salt systems were carried out in the temperature range of 303 to 373 K. The conductivity versus temperature plots obeyed an Arrhenius type variation. The structural and complex formations were studied by X-ray diffraction (XRD) and Fourier Transform Infrared (FTIR) spectroscopy.